2016
DOI: 10.1007/s00394-016-1292-z
|View full text |Cite|
|
Sign up to set email alerts
|

Cheese consumption and risk of cardiovascular disease: a meta-analysis of prospective studies

Abstract: This meta-analysis of prospective studies suggests a nonlinear inverse association between cheese consumption and risk of CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 62 publications
6
68
0
5
Order By: Relevance
“…64 However, several recent meta-analyses as well as a systematic review of the evidence on dairy and health outcomes independent of a dietary pattern have reported significant protective associations between both highand low-fat dairy as well as cheese and yogurt intake, in particular with cardiovascular outcomes. [71][72][73][74] Economic costs associated with adhering to an improved diet, in terms of grocery and preparation costs, implementation costs, or macro-level policy implications of shifts in demand for component foods were not considered in the current evaluation. The current evaluation is theoretical and intended to illustrate the potential economic influence on direct and indirect health-related costs of an increase in the US population's conformance to the 2015-2020 DGA recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…64 However, several recent meta-analyses as well as a systematic review of the evidence on dairy and health outcomes independent of a dietary pattern have reported significant protective associations between both highand low-fat dairy as well as cheese and yogurt intake, in particular with cardiovascular outcomes. [71][72][73][74] Economic costs associated with adhering to an improved diet, in terms of grocery and preparation costs, implementation costs, or macro-level policy implications of shifts in demand for component foods were not considered in the current evaluation. The current evaluation is theoretical and intended to illustrate the potential economic influence on direct and indirect health-related costs of an increase in the US population's conformance to the 2015-2020 DGA recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Further, given the uncertainty inherent in combining risk estimates from individual studies based on the highest and lowest quantiles of conformance, a linear dose response analysis was preferential if both the dose response along with a high versus low comparison was available. Of the 19 studies, eight [10,12,[17][18][19][20][21][22] were excluded for reasons including either earlier publications and/or with fewer studies included, limited to a high estimates from individual studies based on the highest and lowest quantiles of conformance, a linear dose response analysis was preferential if both the dose response along with a high versus low comparison was available. Of the 19 studies, eight [10,12,[17][18][19][20][21][22] were excluded for reasons including either earlier publications and/or with fewer studies included, limited to a high versus low comparison of intake or reported neutral associations between a dairy product and the health outcome.…”
Section: Identification Of Health Outcomesmentioning
confidence: 99%
“…To metaanalyser undersøkte kun sammenhenger mellom meieriprodukter og risiko for hjerneslag 172,173 . Én metaanalyse omhandlet kun ost 174 mens én metaanalyse omhandlet kun melk og syrnede melkeprodukter (inkl. yoghurt) 171 .…”
Section: Meieriprodukter Og Risiko For Hjerte-og Karsykdomunclassified
“…Fire metaanalyser konkluderte med at meieriprodukter var forbundet med lavere risiko for hjerte-og karsykdom (hendelser og/eller død) [174][175][176][177] ; hos Soedamah-Muthu og medarbeidere 175 gjaldt denne sammenhengen melk, hos Chen og medarbeidere ost 174 , mens Qin og medarbeidere fant en gunstig sammenheng mellom meieriprodukter generelt og hjerte-og karsykdom 176 . Alexander og medarbeidere fant derimot ingen signifikant sammenheng mellom meieriprodukter generelt og samlet hjerte-og karsykdom.…”
Section: Meieriprodukter Og Risiko For Hjerte-og Karsykdomunclassified
See 1 more Smart Citation